2010
DOI: 10.1161/hypertensionaha.109.137760
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Volume Combined With Atrial Pump Function Identifies Hypertensive Patients With a History of Paroxysmal Atrial Fibrillation

Abstract: Abstract-Identifying patients at high risk for the occurrence of atrial fibrillation is one means by which subsequent thromboembolic complications may be prevented. Left atrial enlargement is associated with progression of atrial remodeling, which is a substrate for atrial fibrillation, but impaired atrial pump function is also another aspect of the remodeling. Our objective was to differentiate patients with a history of paroxysmal atrial fibrillation using echocardiography. We studied 280 hypertensive patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
59
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 49 publications
3
59
0
5
Order By: Relevance
“…Various clinical and echocardiographic studies have suggested that any diastolic dysfunction accompanying these parameters may affect the LA structure and function in a way to lead to atrial fibrillation and the recurrence of AF after the cardioversion (12)(13)(14). The echocardiographically determined LA size is known to be closely associated with the development of AF, and the LA size has been reported to be an independent predictor of the sinus rhythm restoration after the cardioversion (15,16). The moderate correlation observed between the LAVI and the energy level required for a successful ECV in our study, as well as the higher risk for the recurrence of the AF during the follow-up of the patients in which higher energy levels were needed in order to achieve the sinus rhythm, point to a relationship between the LAVI and the electrical instability.…”
Section: Discussionmentioning
confidence: 99%
“…Various clinical and echocardiographic studies have suggested that any diastolic dysfunction accompanying these parameters may affect the LA structure and function in a way to lead to atrial fibrillation and the recurrence of AF after the cardioversion (12)(13)(14). The echocardiographically determined LA size is known to be closely associated with the development of AF, and the LA size has been reported to be an independent predictor of the sinus rhythm restoration after the cardioversion (15,16). The moderate correlation observed between the LAVI and the energy level required for a successful ECV in our study, as well as the higher risk for the recurrence of the AF during the follow-up of the patients in which higher energy levels were needed in order to achieve the sinus rhythm, point to a relationship between the LAVI and the electrical instability.…”
Section: Discussionmentioning
confidence: 99%
“…In Framingham Heart Study, the duration of elevated BP as well as the level of systolic BP were associated with the development of left atrial dilatation. 24 Moreover, diastolic dysfunction, 25,26 left atrial enlargement and mechanical function, 27 and LVH 28 are all important predictors for the development of AF in patients with hypertension. On the other hand, the development of AF in hypertensive patients with left ventricular diastolic and/or systolic dysfunction can further worsen the left atrial enlargement, and thus increased the risk of AF recurrence.…”
Section: Hemodynamic Changes In Atriamentioning
confidence: 99%
“…4 Furthermore, investigators have shown that evaluating LA pump function combined with LAV enables a more accurate diag nosis of paroxysmal AF (PAF) than do conventional values. 5,6 However, data are sparse concerning the role of functional LA remodeling in predicting procedural outcomes.Identifying the arrhythmic substrates and evaluating the structural and functional changes in the atria by means of noninvasive methods can be useful in selecting patients for rhythmcontrol therapy, including CA, early in the disease process.7 Mul tislice computed tomography (MSCT) is an accurate method for evaluating LAV, with low interobserver variability. In this study, we used MSCT to quantify LA pump function and structural changes before CA.…”
mentioning
confidence: 99%
“…4 Furthermore, investigators have shown that evaluating LA pump function combined with LAV enables a more accurate diag nosis of paroxysmal AF (PAF) than do conventional values. 5,6 However, data are sparse concerning the role of functional LA remodeling in predicting procedural outcomes.…”
mentioning
confidence: 99%